Functional organic material for roxarsone and its derivatives recognition via molecular imprinting. Issue 3 (22nd March 2017) - Fan, Weigang; Zhang, Xuemin; Zhang, Yagang; Wang, Penglei; Zhang, Letao; Yin, Zhaoming; Yao, Jun; Xiang, Wei
Abstract: Roxarsone, one of feed add drugs containing arsenic, has been most widely used in poultry and swine industry. Roxarsone discharged into the environment has caused serious pollution problem. Herein, a reusable functional material for selective recognition and adsorption of roxarsone and its derivatives were designed and synthesized. The interaction mechanism is based on acid‐base interaction and surface molecular imprinting. Dual functionalized core‐shell structure with silica gel as the core was prepared to use as carrier for surface molecularly imprinted polymers. Surface molecularly imprinted polymers for roxarsone was successfully designed and synthesized using 3‐aminopropyltriethoxysilane and methyl acryloyloxypropyltriethoxy silane as functional monomers, Ethylene glycol dimethacrylate as crosslinker, Azobisisobutyronitrile as initiator, acetonitrile as solvent. Binding study showed that the recognition selectivity for roxarsone and its derivatives can be significantly improved (3.5‐4 folds) with molecular imprinting. Moreover, the prepared functional material for selective recognition and adsorption of Roxarsone was reusable for multiple times without significant decreasing their adsorption capacities. Abstract : Cartoon depicts a reusable functional organic material for roxarsone and its derivatives' recognition.